我国食用植物油供给现状分析及未来发展战略研究Present situation of edible vegetable oil supply in China and its future development strategy - 张洋1，严茂林2，葛玮玮1，陈畅1，张志丹2，田恬2，吴成亮1 ZHANG Yang1, YAN Maolin2, GE Weiwei1, CHEN Chang1, ZHANG Zhidan2, TIAN Tian2, WU Chengliang1 (Zhongguo youzhi, 2022)
近年来，伴随着我国食用植物油自给率的持续走低，提高我国本土食用植物油料的供给、保障国家食用油安全上升为国家战略。通过梳理前人研究和官方信息，整理出2000—2019年我国传统八大食用植物油料的产量数据，并结合相关研究计算得出对应历年食用植物油本土供应量，同时建立Holt双参数线性指数平滑模型对我国本土食用植物油料和油脂的总供给进行预测，结合国家食用植物油发展规划，进一步分析当前制约我国食用植物油发展的因素，并提出针对性建议，以期为国家制定食用植物油料油脂发展规划，提高我国食用油自给率提供数据参考和技术支持。In recent years, with the continuous decline in the self-sufficiency rate of edible vegetable oil, it has become a national strategy to improve the supply of domestic edible vegetable oilseeds and ensure the safety of national edible oil. By combing previous studies and official information, the output data of China’s eight traditional edible vegetable oilseeds from 2000 to 2019 were sorted out, and the local supply of edible vegetable oils over the years in combination with relevant studies was calculated, while a Holt two parameters linear exponential smoothing model was established to predict the total supply of domestic edible vegetable oilseeds and oils. Combined with the national edible vegetable oil development plan, the factors restricting the development of edible vegetable oil in China were further analyzed, and targeted suggestions were put forward. It is expected to provide data reference and technical support for the state to formulate the development plan of edible vegetable oil and improve the self-sufficiency rate of edible oil in China.